Thematic Progression in Systemic Functional Linguistics (SFL) as a Pedagogical Instrument to Augment Case-Solving and Comprehensive Case Analysis Competencies - Thi Nguyen Nhung (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2024)
Systemic Functional Linguistics (SFL), developed by Halliday, conceptualizes language as a social semiotic system that fulfills communicative purposes. In Systemic Functional Linguistics (SFL), Thematic Progression (TP) pertains to the development of themes across sentences to establish coherence and cohesiveness in conversation. Structured argumentation and clarity are crucial in legal education, especially in criminal law. Students at the People’s Police College II (PPC II) studying criminal law must refine their writing skills for assignments, reports, and legal analyses. This research emphasizes the significance of thematic progression in assisting students to compose more organized and coherent legal writings. This research examines the utilization of thematic progression in systemic functional linguistics as an educational instrument to improve cadets' case-solving and comprehensive case analysis abilities in the PPC II criminal law exercises. Thematic progression, which entails the methodical advancement of topics within texts, is essential for creating cohesive and logical legal arguments. By examining several patterns of thematic progression, including constant theme, linear theme, and split theme, students can enhance their capacity to formulate coherent legal speech. This method enhances their understanding of legal papers and facilitates the creation of clear and succinct legal reports. The study offers pragmatic instructions for incorporating thematic progression into criminal law exercises, enhancing communication abilities among law enforcement cadets